2016
DOI: 10.1007/s00068-016-0655-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of fracture pattern on transfusion requirements in hip fractures

Abstract: Patients with IT hip fractures are significantly more likely to require an ABT than those with IC hip fractures. Patients undergoing an intramedullary nail for IT fractures have significantly higher transfusion rates than for other types of operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…Intertrochanteric fractures (3.64 ± 1.60 days), trochatero-diaphysaire (4.60 ± 2.72 days) and basicervical fractures (4.71 ± 2.82 days) (p = 0.336) showed mean values without significant differences between sexes or age groups. In a comparative study of extra and intracapsular fractures, Morris et al (16), identified 39.4% vs. of 22.5% patients (p <0.001) requiring blood transfusions, more frequent among patients requiring intramedullary fixation vs. DHS (67.4 vs. 32.0%, p <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Intertrochanteric fractures (3.64 ± 1.60 days), trochatero-diaphysaire (4.60 ± 2.72 days) and basicervical fractures (4.71 ± 2.82 days) (p = 0.336) showed mean values without significant differences between sexes or age groups. In a comparative study of extra and intracapsular fractures, Morris et al (16), identified 39.4% vs. of 22.5% patients (p <0.001) requiring blood transfusions, more frequent among patients requiring intramedullary fixation vs. DHS (67.4 vs. 32.0%, p <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…A shift from sliding hip to intramedullary nails are also seen in other Scandinavian countries [ 30 , 31 ] resulting in a lower reoperation for complex pertrochanteric fractures [ 32 ]. A higher use of intramedullary nails in the restrictive group may increase the likelihood of having a transfusion [ 24 , 25 , 28 , 33 ]. This would potentially lead to a slightly higher transfusion proportion in the restrictive group.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors: According to the literature (Morris et al, 2017), hidden blood loss in intertrochanteric fracture is associated with other factors such as gender, weight, underlying disease, drug factors; mechanism of injury, damage energy, and fracture type etc. These factors are statistically significant and still controversial currently thus further studies are necessary.…”
Section: Discussionmentioning
confidence: 99%